The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1507/endocrj.46.779
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Nitric Oxide Inhibits Growth Hormone Secretion through Cyclic Guanosine Monophosphate-Dependent Mechanisms in GH3 Cells.

Abstract: Constitutive nitric oxide synthase (NOS) is expressed in rat adenohypophysis and clonal GH3 cells. The mechanisms of action of nitric oxide (NO) to inhibit hormone secretion and the possible role of (6R)-5, 6, 7, 8-tetrahydro-L-biopterin (THB) in the action of endogenous NO were studied in GH3 cells. Inhibiting NOS with N(G)-nitro-L-arginine or trapping NO with oxyhemoglobin enhanced both the basal and TRH-stimulated rat GH release. Sodium nitroprusside did not further decrease either the basal or the TRH-stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…This view is supported by in vitro studies showing that NOergic neurons play a permissive role in the medial basal hypothalamus to stimulate the release of many regulatory peptides, as corticotrophin-releasing hormone, luteinizing hormone releasing-hormone, GHRH, somatostatin and oxytocin (46). NO, however, has also been reported in some (18,47), though not all (7,48), studies to inhibit GHRH-induced GH release from rat pituitary cell cultures and to affect basal and dopamine inhibition of prolactin secretion (5).…”
Section: Discussionmentioning
confidence: 93%
“…This view is supported by in vitro studies showing that NOergic neurons play a permissive role in the medial basal hypothalamus to stimulate the release of many regulatory peptides, as corticotrophin-releasing hormone, luteinizing hormone releasing-hormone, GHRH, somatostatin and oxytocin (46). NO, however, has also been reported in some (18,47), though not all (7,48), studies to inhibit GHRH-induced GH release from rat pituitary cell cultures and to affect basal and dopamine inhibition of prolactin secretion (5).…”
Section: Discussionmentioning
confidence: 93%
“…Ghrelin is a significant factor in the function and growth of the adenomas over expressing GHS-R [17]. Tsumori et al [18] reported that NO played an inhibitory role in basal GH release and TRH-stimulated hormone release in an autocrine or paracrine fashion through a cGMP-dependent pathway in GH3 cells. However, some studies show that NO enhances the basal and ghrelininduced GH secretion in cultured somatotrophs [19] and cultured human GH-secreting adenomas [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Tsumori et al . (17), NO scavenging and cGMP antagonists increased agonist‐induced GH release leading to the conclusion that NO inhibits GH release through a cGMP‐dependent mechanism. By contrast, Pinelle et al .…”
Section: Discussionmentioning
confidence: 99%
“…(16) reported that NO‐stimulated GH secretion from rat hemipituitaries in vitro was unaffected by inhibitors of the GC/cGMP cascade and not mimicked by cGMP, suggesting that NO stimulates GH through a cGMP‐independent mechanism. By contrast, a study with GH 3 cells showed that a NO scavenger increased both basal and stimulated GH release, and that a cGMP antagonist increased stimulated GH secretion (17). This suggests that NO acts through cGMP to inhibit GH secretion.…”
mentioning
confidence: 99%